Elastic TPU Mesh as Abdominal Wall Inlay Significantly Reduces Defect Size in a Minipig Model. Issue 6 (18th August 2019) - Heise, D.; Eickhoff, R.; Kroh, A.; Binnebösel, M.; Klinge, U.; Klink, C.D.; Neumann, U.P.; Lambertz, A.
ABSTRACT: Background : The open abdomen with mesh implantation, followed by early reoperation with fascial closure, is a modern surgical approach in difficult clinical situations such as severe abdominal sepsis. As early fascial closure is not possible in many cases, mesh-mediated fascial traction is helpful for conditioning of a minimized ventral hernia after open abdomen. The aim of this study was to evaluate the clinical utilization of an innovative elastic thermoplastic polyurethane mesh (TPU) as an abdominal wall inlay in a minipig model. Methods : Ten minipigs were divided in two groups, either receiving an elastic TPU mesh or a nonelastic polyvinylidene fluoride (PVDF) mesh in inlay position of the abdominal wall. After 8 weeks, mesh expansion and abdominal wall defect size were measured. Finally, pigs were euthanized and abdominal walls were explanted for histological and immunohistochemical assessment. Results : Eight weeks after abdominal wall replacement, transversal diameter of the fascial defect in the TPU group was significantly smaller than in the PVDF group (4.5 cm vs. 7.4 cm; p = 0.047). Immunhistochemical analysis showed increased Ki67 positive cells ( p = 0.003) and a higher number of apoptotic cells ( p = 0.047) after abdominal wall replacement with a TPU mesh. Collagen type I/III ratio was increased in the PVDF group ( p = 0.011). Conclusion : Implantation of an elastic TPU mesh as abdominal wall inlay is a promising approach to reduce the size of the ventral hernia after open abdomen by mesh-mediated traction. However, this effect was associated with a slightly increased foreign body reaction in comparison to the nonelastic PVDF.